Turning the Tide on Poverty: The role of the Cooperative Extension Service in the initiative. Issue 3 (26th May 2016) - Welborn, Rachel; Downey, Laura; Dyk, Patricia Hyjer; Monroe, Pamela A.; Tyler-Mackey, Crystal; Worthy, Sheri L.
Abstract: Cooperative Extension Services (CES) played a critical role in the Turning the Tide on Poverty (Tide) project in the southern US. In an effort to explore how CES professionals perceived their role in the initiative, data were collected from CES leaders and agents. Focus groups were held at the beginning ( N = 11) and conclusion ( N = 12) of the first year with Extension leadership to discuss their thoughts on CES' role in civic engagement activities. Survey data were collected from Extension agents ( N = 17) to gauge attitudes and beliefs during the course of Tide. Leadership and agents noted potential to expand and strengthen outreach through Tide but also expressed concerns about constraints. Implications are that Tide provided a way to enhance the mission of CES and that community development efforts implemented through Tide could be replicated by other CES.